Chronic Low Back Pain: Investigating the Influence of Lifestyle and Physical Activity on Factors that Exacerbate or Enhance Patient Outcomes. - Chwaliszewski, Kamil; Fikas, Klaudia; Waz, Dorota; Mazur, Michał; Szarłowicz, Jakub; Goliszek, Zofia; Sobek, Karolina Łucja; Tabin-Barczak, Wiktoria; Sokołowska, Aldona; Samuła, Sebastian (Quality in Sport, 2025)
Introduction and Purpose: Low back pain (LBP) is a widespread condition and often leading to chronic low back pain (CLBP) in many cases. Although physical activity has shown significant benefits in reducing pain and improving functionality, additional elements such as mental health and social factors may play an essential role in CLBP management. This review examines the influence of lifestyle modifications on CLBP management, with the aim of providing evidence-based recommendations for clinical practice. Material and Methods: This review was conducted through an extensive search of peer-reviewed literature in PubMed, focusing on studies published from 2020 to 2024. The search included terms like "chronic low back pain,", "lifestyle," "exercise," and others. Studies were included if they evaluated the effects of physical activity and lifestyle interventions on pain relief and functional outcomes in LBP patients. Results: The results indicate that exercise treatment is more effective compared to no treatment, usual care, or placebo, particularly in reducing pain intensity. Lifestyle modifications, such as improving sleep quality, adopting healthy dietary habits and managing obesity, may further enhance patient outcomes by addressing additional factors contributing to the complexity of CLBP. Conclusions: Exercise appears to be moderately effective in managing chronic low back pain compared to no treatment, usual care, or placebo. These findings suggest that while exercise can be beneficial, its overall impact may vary depending on the treatment context. The integration of lifestyle factors such as mental health support, addressing sleep disturbances, promoting healthy dietary habits, and managing obesity could significantly enhance the overall effectiveness of CLBP management. Cannabinoids show potential as an alternative or adjunct treatment for CLBP. Physiotherapy interventions support an active lifestyle and enhance physical function in patients.